HISTOPATHOLOGICAL CORRELATION OF LUPUS NEPHRITIS WITH EXTRA-RENAL MANIFESTATION AND LABORATORY FINDINGS - Mirza, Raouf Rahim (Journal of Sulaimani Medical College, 2017)
Background Lupus nephritis is one of the most serious manifestations of Systemic lupus erythematosis and it is a major cause of morbidity and mortality. Objectives To find out the relation between Histopathologyical classes of Lupus nephritis with renal, extra renal clinical manifestation and laboratory data. Patients and Methods A cross-sectional study performed on 45 patients with biopsy proven lupus nephritis, which they were collected from April 2012 to April 2013. Results The current study shows female predominance 32 (71.1%) compared with 13 (28.9%) male. Class IV 15 (33.3%) was the most common type followed by class III 9 (20.9%). The new onset hypertension was the commonest clinical renal presentation 32 (71.1%) and the musculoskeletal manifestation 37 (82.2%) was the most common extra renal manifestation. The correlation between classes of Lupus nephritis with clinical and laboratory data were significant for hypertension, 24 hrs urinary protein excretion, S. Creatinine, S. Albumin, Anti-Sm and Anti-dsDNA positivity and low complement levels (C3, C4). Conclusion Class IV is the commonest class of Lupus nephritis. Female preponderance becomes less pronounce in lupus nephritis compared to prevalence SLE.
Keywords: Systemic lupus erythematosis; Lupus nephritis; Histopathological classification